Implementasi Kebijakan Pengupahan Oleh Dinas Tenaga Kerja Kota Tasikmalaya - Muhammad Fahmi Ashiddiqi; Mawar Mawar (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
This research is motivated by the lack of optimal implementation of wages in accordance with the basic minimum wage in Tasikmalaya City. The problem that was found was the lack of information about the amount of the City Minimum Wage that the company must provide to employees. The purpose of this study is to find out how the implementation of the Governor of West Java Regulation regarding the determination of the provincial minimum wage and the city minimum wage, and then the researcher also wants to know the extent of the policies of the Tasikmalaya City Government, especially the Tasikmalaya City Manpower Office, in realizing Law N0 13 of 2003 concerning Manpower. This study uses a qualitative method with a descriptive approach. The data obtained was carried out by observation, interviews, and documentation. The theory used in the analysis is the Van Metter and Van Horn Theory which consists of several indicators, namely: a) Policy Standards; b) Resources; c) Relations between Organizations; d) Characteristics of the implementing agent; e) Economic, social and political environmental conditions; f) the disposition of the executor. The results of the study show that policy standards and objectives have not felt a significant impact from existing regulations. Then human resources, budget, and materials at the Tasikmalaya City Manpower Office have not run optimally. Relations between organizations have gone quite well. The characteristics of the implementer have not been properly implemented, especially to the labor union. The disposition of the implementer has carried out programs that have referred to the needs of wages in the lake city, but there needs to be realistic and preventive measures taken in an effort to socialize wages and employment. Likewise, economic, social and political conditions that are quite supportive of the implementation of wages where the lake area itself has supporting human resources and natural resources.